(3eNJUQ cTa GdbfGYs - (3eLghds
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd GdUdGI eaJGM OGQ GdSdGe heYQGL Cgd GdESdGe s
(3BNQgG (B:s
(3fQLh ef cQeg hEMSGfg Cf jLYdfG KGHJkG Ydi Ojf GdESdGe hjNJe dfG Ydi MSf GdNJGe HMQeI QShdg Ydjg GdUdGI hGdSdGe s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
(3GNJUGQ s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdMfajs